INCLUSIVE MEASUREMENTS OF THE K+/- AND P/(P)OVER-BAR PRODUCTION IN HADRONIC Z(0) DECAYS - Abreu, P; Adam, W; Adye, T; Agasi, E; Ajinenko, I; Aleksan, R; Alekseev, G; Allport, P; Almehed, S; Alvsvaag, S; Amaldi, U; Amato, S; et al. (1995)
This analysis, based on a sample of 170000 hadronic Z0 decays, provides a measurement of the K± and p/p differential cross sections which is compared to string- and cluster fragmentation models. The total multiplicities for K± and p/p per hadronic event were found to be: NK = 2.26 ± 0.18 and Np = 1.07 ± 0.14. The positions ξ* of the maxima of the differential cross sections as a function of ξ = ln(1/xp) for K± and p/p were determined to be 2.63 ± 0.07 and 2.96 ± 0.16 respectively. A comparison of the ξ* values for various identified particles measured at LEP with the prediction of the Modified Leading Logarithm Approximation with Local Parton Hadron Duality model has been performed. The measured ξ* position as a function of the hadron mass, after corrections due to particle decays, is in agreement with the model calculation. © 1995.